UJI FITOKIMIA DAUN TURI MERAH (SESBANIA GRANDIFLORA L. PERS) - Rina Mardiana, Heppy; Suryani, Lilis (PRIMA WIYATA HEALTH, 2022)
pandemic has made students less active in conveying their aspirations and thoughts which makes students feel bored. The purpose of the study was to determine the relationship between academic stress and student motivation in online learning during the covid-19 pandemic at STIKes Husada Jombang. This research uses a correlational analysis research design with a cross sectional approach. The research population was all students of STIKes Husada Jombang S1 Nursing and D3 Midwifery, with a sample of some students as many as 45 people. The sampling technique used is probability sampling with the simple random sampling method. Data collection using questionnaires and data analysis with Spearmen Rank test. Based on the Spearmen Rank test showsr value 0.000 (rvalue < 0.05). So H1 is accepted, which means that there is a relationship between academic stress and student learning motivation in online learning during the covid-19 pandemic at the STIKes Husada Jombang. Based on this research, it is known that the academic stress level most experienced by respondents is high stress, while for learning motivation the most experienced by respondents is low learning motivation. There is a relationship between academic stress and student learning motivation in online learning during the covid-19 pandemic at the STIKes Husada Jombang. From the results of this study, it is expected that students can learn and understand good stress management in dealing with stress and educational institutions can create a comfortable teaching and learning atmosphere with new learning methods so that students do not feel bored in online learning.